Islamic Perspective on Stylistic Analysis of Verbal Abused in the Movie ‘The Glory by Kim Eun-Sook’s: A Psycholinguistics View - Siti Ithriyah; Septi Fitri Meilana (Dinasti International Journal of Education Management And Social Science, 2024)
Islam is a humanity, a society, and a belief system all in one. Islam provides different points of view on the interactions of science, technology, and ethnics. Islam is a religion that the sees learning as a pathway to both personal and societal salvation. It rejects perceiving any distinction between the religion and the secular in the context of knowledge, striving, upon the guiding principle of the unity of Islamic perspective. A stylistic analysis is a type of linguistic analysis that focuses on the language use and style of a particular text, speech or discourse. The analysis involves examining the linguistic features and choices made by the writer or speaker, including the choice of words, sentence structure, figurative language, tone, and rhetorical devices used to create meaning and effect. Stylistic analysis, a type of linguistic analysis, focuses on the language use and style of a particular text, speech, or discourse. This involves examining linguistic features and choices made by the writer or speaker, such as word choice, sentence structure, figurative language, tone, and rhetorical devices, to understand how these elements contribute to the overall meaning and impact of the piece. Verbal abuse, defined as the use of words or language to harm, intimidate, or belittle another person, can occur in various settings and has serious negative effects on emotional, mental, and physical well-being. "The Glory" tells the story of a high school student who dreams of becoming an architect but becomes a victim of severe bullying, leading her to drop out and plan revenge on her tormentors. A high school student in The Glory had aspirations of becoming an architect after graduation. She fell prey to the brutality inflicted upon her by her classmates throughout her time in high school. Due to the bullying, she decided to leave high school. She proceeded to plot vengeance on her abusers and the apathetic onlookers. This former pupil is now a grown-up. She has patiently awaited the marriage and procreation of her oppressors' leader. The little one has progressed to the elementary school level. The woman who was bullied in school is now her abuser's child's homeroom teacher. She launches into her ruthless scheme of vengeance.